Learning from the STRIDER trial. Issue 8 (August 2019) - Sharp, Andrew; Cornforth, Christine; Alfirevic, Zarko
Abstract: The STRIDER is an international consortium of five randomised trials of the use of sildenafil to treat fetal growth restriction. We describe the scientific rationale and processes undertaken to take advantage of such a joint approach to studying new interventions in pregnancy. We also describe the challenges faced during recruitment and the further challenges faced after initial publication. We discuss concerns about fetal wellbeing identified in the Netherlands STRIDER trial and the implications of this on other studies and the wider maternity research community.